2020
DOI: 10.1021/acs.joc.9b03367
|View full text |Cite
|
Sign up to set email alerts
|

2H-Azirine-2-carbonyl Azides: Preparation and Use as N-Heterocyclic Building Blocks

Abstract: 2H-Azirine-2-carbonyl azides, new reactive heterocyclic building blocks, were synthesized in high yield by the reaction of sodium azide with 2H-azirine-2-carbonyl chlorides, generated by the Fe­(II)-catalyzed isomerization of 5-chloroisoxazoles. 2-(Azidocarbonyl)-1H-pyrroles, prepared by the Ni­(II)-catalyzed reaction of 2-(azidocarbonyl)-2H-azirines with 1,3-diketones, easily undergo the Curtius rearrangement in boiling tBuOH to give Boc-protected α-aminopyrroles in high yield. Heating of 2-(azidocarbonyl)-1H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 22 publications
0
14
0
Order By: Relevance
“…The selectivity of the nucleophilic reaction at the carbonyl group of the 2 H ‐azirine‐2‐carbonyl chloride with pyrazole was controlled by thermodynamic factors [102]. Another reactive heterocyclic building blocks, 2 H ‐Azirine‐2‐carbonyl azides were prepared in presence of sodium azide and 2 H ‐azirine‐2‐carbonyl chlorides in acetone through Fe(II)‐catalyzed isomerization of 5‐chloroisoxazoles [103]. Same group synthesized diazo‐containing azirines compound 2‐(diazoacetyl)‐2 H ‐azirines that involves the reaction of azirine‐2‐carbonyl chlorides with N ‐isocyano triphenyl iminophosphorane followed by treatment of the formed hydrazidoyl chloride with Et 3 N in the presence of TsCl as a catalyst (Scheme 81) [104].…”
Section: From Isoxazolesmentioning
confidence: 99%
“…The selectivity of the nucleophilic reaction at the carbonyl group of the 2 H ‐azirine‐2‐carbonyl chloride with pyrazole was controlled by thermodynamic factors [102]. Another reactive heterocyclic building blocks, 2 H ‐Azirine‐2‐carbonyl azides were prepared in presence of sodium azide and 2 H ‐azirine‐2‐carbonyl chlorides in acetone through Fe(II)‐catalyzed isomerization of 5‐chloroisoxazoles [103]. Same group synthesized diazo‐containing azirines compound 2‐(diazoacetyl)‐2 H ‐azirines that involves the reaction of azirine‐2‐carbonyl chlorides with N ‐isocyano triphenyl iminophosphorane followed by treatment of the formed hydrazidoyl chloride with Et 3 N in the presence of TsCl as a catalyst (Scheme 81) [104].…”
Section: From Isoxazolesmentioning
confidence: 99%
“…On the final stage of this domino sequence dehydration of C leads to formation of pyrroles 139 . The same group of authors [47] developed Ni(II)‐catalyzed reaction of substituted 2 H ‐azirine‐2‐carbonyl azides 144 with 1,3‐dicarbonyl compounds 20 for the synthesis of 2‐(azidocarbonyl)pyrroles 146 . Co(acac) 2 ‐catalyzed reaction of compounds 20 with 2‐(benzotriazole‐1‐ylcarbonyl)‐2H‐azirines 143 produced 2((benzotriazole‐1‐yl)carbonyl)pyrroles 145 in moderate to good yields (Scheme 49).…”
Section: Intra(inter)molecular and Related Reactionsmentioning
confidence: 99%
“…Rearrangements of 2 H -azirines with any substituents leading to heterocycles containing more than two nitrogen atoms are, to the best of our knowledge, still unknown . Recently the synthesis of 2 H -azirine-2-carbonyl azides was developed and used for the preparation of polyheterocycles . It was found that when azide 1a was heated in MeOH or tert -BuOH to obtain the corresponding azirin-2-ylcarbamate via Curtius rearrangement, it led to extensive tarring.…”
mentioning
confidence: 99%
“…1 Recently the synthesis of 2H-azirine-2-carbonyl azides was developed and used for the preparation of polyheterocycles. 7 It was found that when azide 1a was heated in MeOH or tert-BuOH to obtain the corresponding azirin-2ylcarbamate via Curtius rearrangement, it led to extensive tarring. But recently by serendipity we found that 3-phenyl-2Hazirine-2-carbonyl azide 1a in MeOH at room temperature undergoes a quite unusual reaction leading to the formation of methyl 2-(5-phenyl-1H-tetrazol-1-yl)acetate 2a (59%) as the main product and azirine 3a (7%) as byproduct.…”
mentioning
confidence: 99%